PENGARUH TINGKAT PENGENCERAN SPERMA AYAM KAMPUNG DENGAN NaCl FISIOLOGIS YANG DITAMBAH PENISILIN DAN STREPTOMISIN TERHADAP KUALITAS SPERMA PADA SUHU PENYIMPANAN 5Â°C - , M.AFRIZAL A.K. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The objective of this research was to determine the effect of semen domestic chicken dilution rate using physiological NaCl added with penicillin and streptomycin on semen quality at temperature 5ÂºC. Semen were collected and pooled from 4 cock. The treatments of sperm dilution rate conducted were 1:1 (P 1:1), 1:2 (P 1:2), 1:3 (P1:3). Each dilution were added by penicillin and streptomycin at doses 0,05 and 0,05 g/100 ml of diluent (A 1)